PRINCIPLES OF INTRODUCTION OF THE CONTEXT TEACHING IN THE PROCESS OF TRAINING THE FUTURE TEACHERS OF THE PRIMARY SCHOOL - Oksana Kilichenko (Vasyl Stefanyk Precarpathian National University, 2018)
The analysis of state, scientific sources and practical experience in organizing the pedagogical education testifies to the necessity to create such an educational environment in the institutions of higher education, which contributes to the formation of the desire of future primary school teachers not only to acquires profound theoretical knowledge, methods of the organization of the educational process in primary school but also to be able to implement them in their pedagogical activity.To create an educational environment that promotes the formation of a competent teacher helps the use of the context teaching in the process of training of primary school specialists.Contextual education of the future teacher of elementary school includes the system of functioning of all components of the pedagogical process, which is algorithmically sequenced by certain actions aimed at reproduction of the practical and social contexts of future professional activities in the process of professional training.The implementation of context-based teaching in the training of future primary school teachers is carried out through the process of adhering to the principles.Principles of organizing a pedagogical process means a system of regulations that determine the choice of ways, forms, methods and tools for its optimal organization.There distinguished the traditional and innovative principles of organization of context teaching.As a result of the analysis of different approaches to the definition of the principles of the оrganization of context teaching in the process of training future educators, it should be emphasized that сurrently there is no systematic and consistent list of them.The following principles of organizing the training of future teachers of elementary school with the use of context-based teaching are relevant: the principle of science; the principle of continuity, consistency and systematicity, the action of which is aimed at consolidating previously acquired knowledge, experience, skills, personal qualities, their consistent development and improvement; the principle of communication teaching with life, practical activities, the main requirement for adherence to this principle provides for a permanent focus on the practical activities of teachers, studying, investigation of the pedagogical experience; principle of visibility; the principle of the consciousness of the education of future primary school teachers; the principle of the variability of methods and techniques of the organization of the educational process that determines the use of both traditional methods of teaching and interactive teaching methods; the principle of compulsory feedback, which promotes the ability for future teaches of primary school to communicate, express and substantiate their  thoughts, discuss, select the information material and present it in a concrete accessible form; the principle of reflexive education paradigm; the principle of respect for the personality of students in conjunction with reasonable diligence towards them. Key words: process of preparation of future primary school teachers, context learning, context, principles of contextual learning organization.